Paraneoplastic syndrome of renal cell carcinoma in Phramongkutklao Hospital - Mingarcha, Saravut; Kanjanatarayon, Sarayut; Binsri, Nattapong; Siriboonrid, Satit (Insight Urology, 2019)
Introduction : Incidental renal lesion is the most common cause that bring renal cell carcinoma (RCC) patients to urologist and almost of them are asymptomatic. The symptoms of them usually due to locally advanced diseases such hematuria, flank or abdominal pain, palpable mass and the unique presentation of RCC is paraneoplastic syndrome. Objective : To study the prevalence of paraneoplastic syndromes in patients with RCC and association between paraneoplastic syndromes and staging of RCC. Material and Methods : This retrospective study was analyzed 205 patients of RCC in Phramongkutklao hospital during 2007-2017. These data were consisted of paraneoplastic syndromes parameters and pathologic staging. Results : 119 (58%) RCC patients were asymptomatic group and 86 (42%) RCC patients were symptomatic group. The prevalence of paraneoplastic syndromes were 24.4% (elevated ESR 16.6%, hypertension 13.2%, anemia 12.2%, weight loss 10.7%, pyrexia 9.3%, abnormal liver function 12.7%, hypercalcemia 2.9% and polycythemia 0.97%). Symptomatic patients had significantly more paraneoplastic syndromes (odd ratio=11.13) and higher stage(p<0.001). Conclusion : The prevalence of paraneoplastic syndrome was found 24.4% in patients with RCC, elevated ESR is the most common parameter. Symptomatic patients had more paraneoplastic syndromes and higher stage of RCC.